International economic liberalization, distortions and growth in Asean - Fauziah Abu Hasan (Fakulti pengurusan dan Ekonomi, 2012)
Liberalization of the international sector is widely assumed to affect growth positively by reducing distortions and market restrictions. This study analyzes the long-rong relationship between international economic liberalization and growth for the ASEAN region between 1960 and 1986